DEVELOPMENT OF THE BLOOD-BRAIN BARRIER IN THE ONTOGENESIS IN THE LIGHT OF IMMUNOHISTOCHEMICAL ANALYSIS OF NEUROSPECIFIC PROTEINS - D. V. Blinov (Эпилепсия и пароксизмальные состояния)
Abstract: the current concept of the structural and functional organization of the blood-brain barrier (BBB) was discussed in part one of the literature review. In the second part, we describe the development of the BBB concept. Beginning from the twentieth of the last century, the process of accumulation of knowledge about BBB is characterized by progressive increase of fundamental and applied studies on the subject. In order to better understand the role of BBB we must consider its ontogenetic development. Experimental studies addressed this issue by way of verifying the presence of neurospecific antigens to show a gradual formation of the BBB structures when the completion of their formation not always coincide with the time of organism birth. These observations are very important for determination of the role of the BBB “breakthrough” in the occurrence of epilepsy, infantile cerebral paralysis (ICP) and other long-term neurological disorders which can be associated with perinatal hypoxic-ischemic brain injury. Understanding of the ontogeny of the BBB is also important in defining the modern diagnostic and treatment approaches including immunochemical verification of eurospecific proteins (NSP) in biological fluids and neuroprotective therapy.